Strength and high temperature behaviour of carbon composite pellets containing BOF fine dust. (1st September 2014) - Wang, G.; Xue, Q. G.; Zhao, Y. X.; She, X. F.; Wang, J. S.
Abstract: Steel plants produce significant amounts of dust and sludge during iron and steel production. These wastes contain valuable elements, such as Fe, Cr, Ni, C, K and Na and should be handled properly to prevent them from polluting the environment. In order to utilise the BOF fine dust, the effects of the dust on cold bonded pelletising, solid state reduction and reduction melting behaviours of composite pellets made from iron ore and anthracite with added BOF fine dust were investigated at laboratory scale. The BOF dust was found to improve the cold compressive strength of the wet green carbon composite pellet, and increased with increasing dust content. Almost four times the amount of dust was needed to get the same effect on the strength of the pellet when it was used to replace bentonite. The carbothermic reduction of the composite pellet proceeded effectively at temperatures above 1200°C. The BOF dust had a positive effect on the reduction rate of the pellet, and the rate increased with increased dust content. The reduction of iron oxide was topochemical and conformed to a shrinking core kinetic model. The dust was found to improve the iron and slag melting separation rate of reduced pellets at 1400°C when its content was less than 23·11 wt-%. The liquidus temperature of the slag would decrease with the content of BOF dust increasing from zero to ∼30 wt-% and then increase if the content continued to become more in the experiment. Utilising the BOF dust as the binder and flux to adjust the composition of the slag system can potentially reduce the slag ratio and production cost compared with using bentonite and limestone. This work can help to find a new process for the effective utilisation of BOF dust in a more appropriate and environmentally friendly way.